Going the distance: a cross-sectional geospatial analysis quantifying province-wide inequities in travel-based access, and fragility of access to French-language primary care provided by family physicians in Ontario, Canada - Belanger, Christopher; Timony, Patrick E; Bélizaire, Arlynn; Desilets, Antoine; Fitzsimon, Jonathan Peter; Gauthier, Alain P; Godfrey, Leanda; Karunananthan, Sathya; Kehoe MacLeod, Krystal; Muray, Mwali-Nachishali; Peixoto, Cayden; Bjerre, Lise M (BMJ Open, 2026)
Objectives Language-concordant care, or healthcare in one’s preferred language, is important both for health equity and for improving health outcomes. Linguistic minorities, like Francophones in Ontario, Canada, are at risk of poorer clinical outcomes if they receive non-language-concordant primary care. However, common ratio-based access measures can provide misleading views of minorities’ actual access levels. This cross-sectional geospatial study demonstrates a new way to measure primary care access using average travel time to the nearest five English- and French-speaking family physicians. We also introduce the concept of primary care access fragility, where a region’s primary care access may depend on one or a few local family physicians. Our research question is: are there differences in travel burden and access fragility for census subdivisions (CSDs) across language (English/French), rurality (urban/rural) and region (north/south) in the province of Ontario, Canada? Design We conducted a cross-sectional geospatial analysis to estimate English-language and French-language primary care travel burdens and access fragility in Ontario, Canada. We used population and boundary data from Statistics Canada’s 2021 census, road-network data from OpenStreetMaps, and family physician practice locations and language abilities from the College of Physicians and Surgeons of Ontario. We measured travel burden using Valhalla, an open-source road-network analysis platform. Setting: We conducted our analysis for Ontario, Canada’s 577 CSDs, which correspond roughly to municipalities and with populations ranging from 5 inhabitants in Rainy Lake 17B to a high of 2 794 356 in Toronto. Participants: Using public data from January 2026, we identified 15 762 family physicians practising in Ontario, of whom 11.0% reported speaking French. Patient data were obtained from the most recent 2021 census. Primary and secondary outcome measures: Our first primary outcome measures were CSD-level mean travel time to the nearest five English-speaking family physicians, and CSD-level mean travel time to the nearest five French-speaking family physicians, which we compared to explore regional inequities in travel burden. Our secondary outcome measures were based on a novel notion of the travel burden component of ‘primary care access fragility’. This metric indicates how dependent a region’s access is on a small number of local physicians and is defined as the difference between the CSD-level mean travel time to the nearest one physician and to the nearest five physicians. As the difference in travel times grows, so too does access fragility. Results Median differences in French-language and English-language travel burdens were strongly significant across rurality, regions and overall (median difference 13.4 min, p<0.001, IQR 4.9–29.3 min), as was primary care access fragility (median difference 5.2 min, p<0.001, IQR 0.8–18.4), with larger travel burdens and fragilities in northern and rural communities. Conclusions Compared with the general public, Ontario’s French-speakers face higher travel burdens to language-concordant family physicians and higher access fragility, especially in rural and northern regions. Our results are of interest to policymakers and health-system planners, and our methods are applicable to other populations and regions.

La téléconsultation : un levier pour rehausser l’accès aux services de santé en français pour les communautés francophones en situation minoritaire de l’Ontario - Dorion, Michelle; Giroux, Isabelle; Dionne, Éric (Reflets, 2026)
Les écrits démontrent que l’accessibilité aux services de santé en français est lacunaire chez les communautés francophones vivant en situation minoritaire (CFSM). Cette barrière linguistique est alarmante, car elle peut avoir des conséquences graves sur la qualité des soins et sur la sécurité des patientes et patients francophones. Face à cette réalité, la téléconsultation représente une solution technologique prometteuse permettant d’élargir l’offre des services de santé en français pour les CFSM. Ainsi, cet article présente un point de vue critique quant à l’utilisation de la téléconsultation en abordant les avantages et les limites qui lui sont associés. Les possibilités qu’offre ce dispositif pour rehausser les services de santé en français chez les CFSM seront également abordées en tenant compte des données recueillies auprès de patientes et patients ainsi que des prestataires de soins de santé francophones concernant leurs expériences avec l’utilisation de la téléconsultation à l’Hôpital Montfort, un centre hospitalier francophone en Ontario. Research shows that access to healthcare services in French is deficient in Francophone minority communities. This language barrier is alarming as it can have negative impacts on the quality and safety of care provided for Francophone patients. Faced with this reality, teleconsultation is a promising technological solution to enhance the offer of services in French for Francophone minority communities. Thus, this article presents a critical view on the use of teleconsultation by addressing its associated benefits and limitations. The possibilities this technology offers to enhance health services in French to Francophones living in a linguistic minority community will also be addressed by taking into account the experience with teleconsultation of French-speaking patients and healthcare providers at Montfort Hospital, a Francophone community hospital in Ontario.

Visualisation des données sur l’offre et la demande de services en soins de longue durée en Ontario: un portrait régional de de l'offre et des besoins réalisé à l'aide de la plateforme dynamique Power-BI de Microsoft (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Visualization of data on the supply and demand for French-language long-term care services in Ontario: A regional snapshot of French-language long-term care supply and demand in Ontario,created using Microsoft's dynamic Power-BI platform (version 2025) - Duong, Patrick; Timony, Patrick E.; Belanger, Christopher; Glaude, Normand; Pelbois, Christelle; Bouchard, Louise (Forces-Santé, 2026)

Tableaux de bord : L’offre et la demande de services de santé en français - Soins de longue durée. (Power-BI, version bêta) - Duong, Patrick; Timony, Patrick E.; Glaude, Normand; Bouchard, Louise (Forces-Santé - Vitrine de données, 2026)
Résumé Ce tableau de bord propose une visualition interactive des données afin d'illustrer le potentiel de l'analyse géographique et de mieux compremdre les besoins des communautés francophones de l'Ontario en matière de soins de longue durée, dans une perspective d'équité et d'accès aux services. Abstract This dashboard provides an interactive visualization of data to illustrate the potential of geographic analysis and to better understand the long-term care needs of Ontario's Francophone communities, with a focus on equity and access to services.

Official Language Minority Communities in Ontario: (In)visibility of Nursing Care - Muray, Mwali; Chartrand, Julie; Perron, Amélie (Aporia, 2026)
Despite Canada’s linguistic duality, French-speaking minority populations continue to face significant barriers in accessing equitable health care. Investigating two key research questions, this study explores: (1) What are the lived experiences of registered nurses and nursing students caring for French-speaking patients in Ontario? and (2) How do French-speaking patients navigate the health care system to access care in their preferred language? Using qualitative methodology informed by interpretive phenomenology, 31 participants were interviewed individually between 2018 and 2019, offering firsthand accounts of their experiences. Findings reveal a paradox of (in)visibility: French-speaking patients and nursing providers remain invisible when they adapt to systemic shortcomings but become highly visible when they advocate for equitable care. The study highlights the urgent need for the effective and consistent implementation of the strategic changes within health care institutions. Addressing these linguistic disparities is not only a matter of patient safety and quality care but also a fundamental step toward upholding Canada’s bilingual commitments in health service delivery.

(Re)penser le travail social avec et pour la communauté des adultes autistes francophones de l’Ontario au prisme de la neurodiversité et de l’intersectionnalité : quand les savoirs d’expérience s’entremêlent - Nugent, Bianca (University d'Ottawa, 2026)
Située au croisement des études critiques en autisme, des approches afroféministes intersectionnelles et du travail social en contexte francominoritaire, cette thèse doctorale documente les inégalités sociales complexes (Collins & Bilge, 2016; Nash, 2017) vécues par les adultes autistes francophones en contexte minoritaire ontarien — une population largement absente des écrits scientifiques. Alors que les travaux récents dans le domaine des études critiques en autisme (Freeman Loftis, 2023 ; Milton et Ryan, 2022 ; Woods et Waldock, 2021 ; Gillespie-Lynch et al., 2017; O’Dell et al., 2016 ; Davidson et Orsini, 2013) exposent les injustices épistémiques et la neuronormativité (Catala et al., 2021 ; Claveau, 2024 ; Fricker, 2007), peu d’études francophones ont exploré ces phénomènes hors Québec. Mobilisant une approche intersectionnelle intracatégorielle (Nash, 2008 ; McCall, 2005), ainsi que les savoirs d’expérience autistiques (Catala, 2025 ; Botha et al., 2024 ; Kapp, 2020 ; Yergeau, 2017 ; Milton, 2014), cette recherche critique adopte une posture éthique et inclusive avec et pour les adultes autistes en recherche centrée sur les communautés (Cascio et al., 2020 ; Raymaker, 2016 ; Raymaker et Nicolaidis, 2013). Elle repose sur une méthodologie qualitative multimodale (sondages, autoentrevues, entretiens semi-dirigés et une rencontre de groupe) menée en Ontario auprès de vingt-quatre participant·e·s : douze adultes autistes ; six proches aidantes, dont cinq mères et une sœur d’un jeune adulte autiste ; six intervenant·e·s des domaines sociaux et communautaires francophones de l’Ontario. Au regard de l’offre active des services en français et de l’intervention sociale en contexte linguistique minoritaire (Reaume et al., 2024 ; Savard et al., 2024 ; Benoît et van Kemenade, 2017 ; Savard et al., 2015 ; Drolet et al., 2010), la thèse postule que les adultes autistes francophones de l’Ontario sont en situation de « surminorisation autistique francominoritaire ». Ce phénomène renvoie à l’invisibilisation sociale, linguistique et épistémique, lors que les personnes autistes francominoritaires se retrouvent exclues par les cadres anglonormatifs de l’autisme et brimées de leurs droits de minorités linguistiques (Forgues et Maillet, 2024 ; Baril, 2017a) devant des services en français généralistes peu adaptés à leur neurodivergence. Les résultats révèlent leurs parcours marqués par le désalignement et la rareté des services et des ressources en français en Ontario conjugué au manque de reconnaissance des réalités distinctes et des obstacles d’accès accrus pour les personnes autistes racisées, migrantes, de la pluralité de genre et de la diversité sexuelle ou résidant hors des grands centres. Leurs savoirs expérientiels recueillis ont permis de formuler des leviers d’action pour transformer les pratiques en travail social ; renforcer l’offre active de services et des ressources ; et informer les politiques publiques dans une perspective intersectionnelle, plurilinguistique et inclusive en contexte linguistique minoritaire. Cette thèse contribue au bassin émergent des études critiques canadiennes en autisme à l’âge adulte à l’intersection de langue, de l’identité, du genre, du statut socioéconomique et d’autres inégalités structurelles observées en contexte francominoritaire. Elle offre des fondements empiriques et théoriques pour une refonte des interventions sociales fondée sur la reconnaissance, l’autodétermination et la légitimation neuroaffirmative des voix des personnes autistes francominoritaires surminorisées.

Access to a telehealth falls prevention program: Mixed-method analysis from a health equity perspective - O’Neil, Jennifer; Dionne, Nathalie; Sauve-Schenk, Katrine; Savard, Jacinthe (Journal of Telemedicine and Telecare, 2026)
Introduction Access to falls prevention programs, addressing an important public health concern, is often limited for Francophone and Acadian minority communities. Technology has been used to deliver falls prevention programs, but health equity factors linked to improving its access for all are still poorly understood. This study aimed to document health equity factors influencing access from the perspective of older francophone adults in various communities across Canada. Methods Guided by the digital health equity framework, we used a sequential explanatory mixed method, including a descriptive sociodemographic questionnaire and semi-structured interviews, to document perspectives on access of persons who had completed different versions of a telehealth falls prevention program. Results Sixty-one participants from five provinces completed the sociodemographic questionnaire, of which most participants (n= 45) represented perspectives from francophone communities living in a minority situation. Results revealed that 91% of participants had access to a computer or tablet with adequate audio-visual components for telehealth. Twenty of these participants, from four provinces, shared their perspectives. The majority of them reported that falls prevention programs should be offered in their preferred language and with different delivery options that consider the social and safety preferences of participants. Eight recommendations informing policy and implementation emerged. Discussion Advocacy around digital connectivity is essential to ensure that all Canadians have equitable access to high-speed internet connections and proper infrastructure. Participants also raised the importance of adapting services to their linguistic realities, geographic location, safety, and basic needs to optimize the impact of the health services provided to them.

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de recherche intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Home Care Experiences and Language Challenges in Ontario: Perspectives of Francophone Seniors, Family Caregivers, Frontline Care Providers, and Managers. Summary report - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.